Enhanced Lithium‐Storage Performance from Three‐Dimensional MoS2 Nanosheets/Carbon Nanotube Paper. Issue 7 (24th June 2014) - Li, Hongsen; Wang, Xiaoyan; Ding, Bing; Pang, Gang; Nie, Ping; Shen, Laifa; Zhang, Xiaogang
Abstract Promising energy‐storage behavior from molybdenum disulfide (MoS2) in the charging and discharging process is attributed to its layered, two‐dimensional structure, which enables convenient electrochemical reactions, but its performance is currently limited by inherent poor electrical conductivity. Herein, we report a facile and efficient method to fabricate a flexible, three‐dimensional, binder‐free electrode architecture consisting of highly conductive carbon nanotube paper conformally covered by MoS2 nanosheets. Its distinct advantages include abundant porous structure, highly conductive pathway for electrons, and fast transport channels for lithium ions. Electrochemical studies confirm that the MoS2 nanosheets/carbon nanotube paper electrode exhibits outstanding performance in terms of specific capacitance, rate capability, and cycling stability.